Analisis Tentang Pengaruh Budaya Kerja, Komitmen Organisasi, Dan Standar Prosedur Operasional Terhadap Produktivitas Kerja Karyawan (Studi Kasus di PT Kimia Farma Apotek Tbk (Persero) Wilayah Bandung Timur) - Kosasih (JRB-Jurnal Riset Bisnis, 2018)
The purpose of this research is to obtain empirical evidence through data analysis of the influence of work culture, organizational commitment, and strandar operational procedures on employee work productivity at PT Kimia Farma Apotek Tbk (Persero) East Bandung Region. The research method used in this research is descriptive and verifikatif method with quantitative approach and using multiple linear regression analysis. Technique of collecting data that is used is by observation at 6 pharmacy chemical pharmacy of East Bandung area through questionnaires completed by interview. the esult of this study indicate that both partially and simultaneously between work culture, organizational commitment and standart operational process have a positive effect on employee work productivity. It means that the more work culture organizational commitment, and ordinary operational procedures, will make the work productivity of employees more and more tense. As well as the most dominant most affecting work productivity is comitment organization, meaning with high organizational commitment, automatically employees will work hard for the company, proud of the company and have good emission ties the company.